Benefit-Risk Summary of Crizotinib for the Treatment of Patients With ROS1 Alteration-Positive, Metastatic Non-Small Cell Lung Cancer. (21st June 2016) - Kazandjian, Dickran; Blumenthal, Gideon M.; Luo, Lola; He, Kun; Fran, Ingrid; Lemery, Steven; Pazdur, Richard
Abstract : On March 11, 2016, after an expedited 5-month review, the U.S. Food and Drug Administration expanded the crizotinib metastatic non-small cell lung cancer (mNSCLC) indication to include the treatment of patients whose tumors harbor a ROS1 rearrangement. The approval was based on a clinically meaningful, durable objective response rate (ORR) in a multicenter, single-arm clinical trial (ROS1 cohort of Trial PROFILE 1001) in patients with ROS1-positive mNSCLC. The trial enrolled 50 patients (age range: 25–77 years) whose tumors were prospectively determined to have a ROS1 gene rearrangement by break-apart fluorescence in situ hybridization (96%) or reverse transcriptase polymerase chain reaction (4%) clinical trial assays. Crizotinib demonstrated an ORR of 66% (95% confidence interval [CI]: 51%–79%) with a median duration of response of 18.3 months by independent radiology review and 72% (95% CI: 58%–84%) by investigator review. Patients received crizotinib 250 mg twice daily and had a median duration of exposure of 34.4 months. The toxicity profile in ROS1-positive patients was generally consistent with the randomized safety data in the U.S. Product Insert from two ALK-positive mNSCLC trials. The most common (≥25%) adverse reactions and laboratory test abnormalities included vision disorders, elevation of alanine transaminase and aspartate transaminase levels, nausea, hypophosphatemia, diarrhea, edema, vomiting, constipation, neutropenia, and fatigue. There were no treatment-related deaths. A favorable benefit-to-risk evaluation led to the traditional approval of crizotinib for this new supplemental indication. Abstract : The FDA has expanded the crizotinib metastatic non-small cell lung cancer indication to include treatment of patients whose tumors harbor a ROS1 rearrangement. The approval was based on a clinically meaningful, durable objective response rate (66%) in a multicenter, single-arm clinical trial. Patients received crizotinib 250 mg twice daily; the median duration of exposure and of response was 34.4 and 18.3 months, respectively.